Rethinking the anthropology of Islam: dynamics of change in Muslim societies ; in honour of Roman Loimeier - Föllmer, Katja; Franke, Lisa Maria; Ben Amara, Ramzi; Stauth, Laura; Loimeier, Roman (ZMO-Studien, 2024)
$uIntro -- Content -- Why Rethinking the Anthropology of Islam? -- Acknowledgements -- Publications of Roman Loimeier -- Congratulants -- Part I: Methodological Reflections on Social Practices and Cultural Productions of Meaning -- In the Event of the Lineage -- Notes Toward a Baraza Sociology ... -- This Is Tanta: Or What I Learned from Acting in an Unprofessional Manner during Fieldwork -- Measuring Risk in Pandemic Times: Social Relationships and Testing Technologies -- Part II. Religion I: Negotiating New Religious Values and Spaces -- Faith-Oriented Schooling as Socio-Moral Intervention -- Tropes of Longing and Loss -- Espaces sacrés et personnification écologique -- (Garden-)Walls: A Study of Religions's Exploration of Constructive Makers of Space -- Part II. Religion II: Agency in the Context of Religious Tradition and Change -- Pioneers of Piety -- 'Speaking for Islam': Three Malams and Their Claims to ʿIlm in a Zongo in Asante -- Between the Sociology of Religious Authority and the Anthropology of Religious Discourse: Abduljabbar Nasiru Kabara and His Blasphemy Trial in Nigeria -- Alternatives to Conveying Religious Knowledge: Islamic Influencers -- Insights from Egypt -- Part III. Society I: Social and Political Aspects of Change, and the Search for Identity from Historical and Cultural Perspectives -- Brushing Max Weber against the Grain in African Historiography: The Case of Pre-Colonial and Colonial Ilọrin -- Of Jewels, Eyeglasses, and Books: Muḥibb al-Dīn al-Khaṭīb as Booktrader and Publisher in the Early 1920s -- Warum der falsche Prophet im Nil ertrinkt: Unorthodoxe Bemerkungen zur postkolonialen Lesart von al-Ṭayyib Ṣāliḥs Roman Mausim al-hiğra ilā l-šimāl -- 'Zanzibaris' in Durban? South African Muslims and Racial Classification in 20th Century South Africa -- Social Movements and Collective Identity: A Cultural Approach -- Part III. Society II: Gendered Agency and Discourses -- 'Honour'-Crime? Femicide? 'Just' Family Violence? Was it the Jinnī in the End? Narratives around a Young Woman's Death in Palestine in 2019 -- Women and the City: Observations on Muslim Women's Lives in Kano (Nigeria) and Bobo-Dioulasso (Burkina Faso) -- Women and the Hajj in Senegal and Burkina Faso since 1980: Strategies, Initiatives, and Perceptions -- Discourse on Women in Tunisia: Between State Feminism, Patriarchy and Islamic Tendencies -- Gendered Expectations: Reflections on Domestic Labour and the Digitalization of Everyday Life in Egypt -- List of Contributors.